(untitled) (Global Journal of Management and Business Research, 2012)
Strategic HR practice is always a challenge for any organization to provide a set of service that is able to make the sense in terms of implementing the organization’s strategic plan. Because without proper evaluation of the term, a company may not find out the challenges and the probable scopes of improvement. In today’s business world we cannot avoid the contribution of strategic practice especially in the service sectors like fast growing banking sector. The banking service in the world is growing day by day. Bangladesh, albeit a developing country, is no exception from it. In the recent period of time Human Resource Management (HRM) practices became so familiar and momentous in every business sector of Bangladesh. The success of every organization is coming through the performance of the employees of that organization. The effectiveness of the employee performance is largely depends upon the HR policy and practices. Therefore, the management should consider the magnitude of strategic HRM practices.